Successful resection of a huge hepatocellular carcinoma during pregnancy: case report and review of the literature - Qihui Hu; Jiaxing Li; Jixing Wang; Cong Chen; Rui Tao (Journal of the Egyptian National Cancer Institute)
Abstract Background Hepatocellular carcinoma during pregnancy is rare and poses significant potential risks to both the pregnant individual and the fetus. Here, we report a case of hepatocellular carcinoma during pregnancy. The 28-week gestational is a critical point of fetal maturation. A literature review revealed no similar case with survival exceeding 2 years, following resection of a large hepatocellular carcinoma diagnosed in late-stage pregnancy. This article may contribute to future research aimed at extending the survival time of patients with hepatocellular carcinoma diagnosed in late pregnancy. Case presentation A 33-year-old pregnant woman was diagnosed with hepatocellular carcinoma at 34 weeks of pregnancy. A cesarean section was performed at 34 weeks of pregnancy. Under general anesthesia, a right lobectomy of the liver was conducted after 15 days. The patient received continuous support from the clinical psychology team throughout the entire perioperative period. The postoperative recovery was smooth, and the patient was discharged without any significant complications. Approximately 2 years post-surgery, follow-up indicated that the patient remained alive and in good health. Conclusions The physiological changes associated with pregnancy can promote rapid tumor growth, leading to poor prognoses. Expert decision-making should be guided by the growth and maturation status of the fetus in relation to hepatocellular carcinoma development. For patients in the late stage of pregnancy, timely termination of pregnancy and tumor resection surgery, along with obtaining assistance from the clinical psychology team during the perioperative period, followed by post-discharge treatment with a combination of Sintilimab and Lenvatinib, constitutes an effective strategy for prolonging patient survival.